Edible Film Application from Red Ginger Starch as Seblak Seasoning Packaging - Melati Savira Habsari; Yelmira Zalfiatri; Dewi Fortuna Ayu; Annisa Nazifa Salman; Cecep Ijang Wahyudin (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2026)
Edible film was a thin layer made from agricultural-based raw materials that was applied as a coating on food components and was directly consumable. Red ginger as a herbal plant contained polysaccharides that had the potential to serve as a starch source. This study aimed to obtain the best edible film formulation with the addition of red ginger starch, which was applied as packaging for seblak seasoning. The research was conducted experimentally using a completely randomized design (CRD) consisting of five treatments and three replications. The treatments included P1 with 0.5 g of red ginger starch, P2 with 1.0 g, P3 with 1.5 g, P4 with 2.0 g, and P5 with 2.5 g. The observed parameters were water vapor transmission rate, thickness, solubility, dissolution time in seblak seasoning, and moisture content of the edible film applied to the seasoning. Based on the results, the selected treatment was P1 (0.5 g red ginger starch), which produced a water vapor transmission rate of 4.58 g/m²•hour, a thickness of 0.18 mm, a solubility of 91.08%, a dissolution time of 1 minute 3 seconds in seblak seasoning, and a moisture index of 0.0711 g on the sixth day.